2020
DOI: 10.3847/1538-4357/abbacb
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Observational Research on Solar Flare EUV Spectra and Geometrical Features

Abstract: We performed statistical analysis on the flare emission data to examine parameters related to the flare extreme-ultraviolet (EUV) spectra. This study used the data from the Geostationary Operational Environmental Satellite X-ray Sensors to determine the fundamental flare parameters. The relationship between soft X-ray data and EUV emission data observed by the Extreme Ultraviolet Variability Experiment on board the Solar Dynamics Observatory (SDO) MEGS-A was investigated for 50 events. The results showed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To find out the parameters that control the properties of flare emission, a statistical analysis on the observed flare emission data was performed to examine flare parameters related to the flare EUV spectra. From this study, it was found that the geometrical features of flare, such as flare loop length and ribbon distance, were found to be essential parameters for predicting flare emission duration (Nishimoto et al 2020).…”
Section: X-rays and Extreme Ultraviolet Emissionsmentioning
confidence: 95%
“…To find out the parameters that control the properties of flare emission, a statistical analysis on the observed flare emission data was performed to examine flare parameters related to the flare EUV spectra. From this study, it was found that the geometrical features of flare, such as flare loop length and ribbon distance, were found to be essential parameters for predicting flare emission duration (Nishimoto et al 2020).…”
Section: X-rays and Extreme Ultraviolet Emissionsmentioning
confidence: 95%
“…The Doppler signals in Sun-as-a-star spectra are also analyzed using the EUV spectral lines taken by the Extreme ultraviolet Variability Experiment (EVE; Woods et al 2012) on board the Solar Dynamics Observatory (SDO; Pesnell et al 2012). SDO/EVE has been mainly used for analyzing a light curve of each EUV line (e.g., Harra et al 2016;Nishimoto et al 2020). Furthermore, many recent studies have firmly established the capability of Doppler analysis for solar active phenomena by SDO/EVE (Hudson et al 2011(Hudson et al , 2022Chamberlin 2016;Cheng et al 2019;Xu et al 2022;Fitzpatrick & Hudson 2023;Lu et al 2023).…”
Section: Introductionmentioning
confidence: 99%